MYH9 Inhibition Suppresses TGF-β1-Stimulated Lung Fibroblast-to-Myofibroblast Differentiation - Sun, Xionghua; Zhu, Mei; Chen, Xihua; Jiang, Xiaogang (Frontiers in Pharmacology, 2021)
Previous cDNA microarray results showed that MYH9 gene expression levels are increased in TGF-β1-stimulated lung fibroblast. Recently, our proteomic results revealed that the expression levels of MYH9 protein are notably upregulated in lung tissues of bleomycin-treated rats. However, whether MYH9 plays a critical role in the differentiation of fibroblast remains unclear. Herein, we demonstrated that TGF-β1 increased MYH9 expression, and siRNA-mediated knockdown of MYH9 and pharmacological inhibition of MYH9 ATPase activity remarkably repressed TGF-β1-induced lung fibroblast-to-myofibroblast differentiation. TGF-β1-stimulated MYH9 induction might be via ALK5/Smad2/3 pathway but not through noncanonical pathways, including p38 mitogen-activated kinase, and Akt pathways in lung fibroblasts. Our results showed that MYH9 inhibition suppressed TGF-β1-induced lung fibroblast-to-myofibroblast differentiation, which provides valuable information for illuminating the pathological mechanisms of lung fibroblast differentiation, and gives clues for finding new potential target for pulmonary fibrosis treatment.